Estudo das ideias de justiça no pensamento político-filosófico de Jean-Jacques Rousseau - Brandão, Caius César de Castro (2015)
The understanding of the origins and foundations of justice in Jean-Jacques Rousseau requires a careful study of the different notions of justice the philosopher seems to make use, particularly in the Discourse on the Origin and Foundations of Inequality Among Men, in Emile, or On Education and in The Social Contract, or Principles of Political Right. First of all, we must identify and delineate more precisely which ideas of justice permeate these works, pointing to the differences and similarities they keep among them. We must also inquire about their genealogies and teleologies. Where appropriate, we should seek to reveal its temporality and extent, but in all cases, we must strive to understand their conditions and modes of existence. A systematic analysis of their constituent elements will contribute to our goal of understanding its essential attributes. To accomplish our goal, we will treat the ideas of justice as objects to be clarified and assign them a typology with which we will systematize our research. Later, the relationships that those different models of justice keep among them will be investigated and how they make up the whole of the political and philosophical thought of Jean-Jacques Rousseau.